2013
DOI: 10.1002/jts.21874
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Exposure to Social Violence and Natural Disaster on Children's Mental Health

Abstract: Disaster mental health, particularly focused on children post disasters, remains an understudied area in developing countries like India. The study compares differential impact of a natural disaster versus a spate of communal riots that occurred in Gujarat on 26 th January 2001 and Feb-June 2002 respectively. Gujarati children of 8-15 years from highly exposed earthquake sites (n = 128) and riot sites (n = 171) were approached for participation.A matched control sample of 351 non-trauma children were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…exposure to violence, media coverage, level of engagement) and post-event circumstances (e.g. loss of personal and social resources, unemployment) (Goldmann and Galea, 2014;Hanson et al, 1995;Kumar and Fonagy, 2013;Lau et al, 2017;Moussa et al, 2015;Ni et al, 2016Ni et al, , 2017Norris et al, 2002aNorris et al, , 2002bNorth and Pfefferbaum, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…exposure to violence, media coverage, level of engagement) and post-event circumstances (e.g. loss of personal and social resources, unemployment) (Goldmann and Galea, 2014;Hanson et al, 1995;Kumar and Fonagy, 2013;Lau et al, 2017;Moussa et al, 2015;Ni et al, 2016Ni et al, , 2017Norris et al, 2002aNorris et al, , 2002bNorth and Pfefferbaum, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to violence was most consistently associated with increased risk of PTSD: direct victims of looting, arson and physical injury demonstrated the highest levels (Kim-Goh et al, 1995;Obilom and Thacher, 2008;Unuvar et al, 2017). Witnessing a personal attack (Kumar and Fonagy, 2013;Obilom and Thacher, 2008), being in close proximity to violence (Moussa et al, 2015) and the level of media exposure (Galovski et al, 2016) were also associated with PTSD risk. Demographic characteristics such as female sex and lower socioeconomic status were associated with increased risk of PTSD among school children (Moussa et al, 2015).…”
Section: Ptsdmentioning
confidence: 97%
See 1 more Smart Citation
“…Only 7.6% of the earthquake sample seemed to fall in the abnormal Strength and Difficulties Questionnaire (SDQ)-Total Difficulties score band in comparison to the 38.7% of riots group and significant differences between the 2 groups were detected. 21 Such rate of MHPs in children was than rate found in another study using the SDQ, which showed that 59.9% of children rated themselves having psychiatric morbidity compared to 61.5% according to parents report. 22 Our study was inconsistent with Agampodi et al 23 study of mental health problems (MHPs) among adolescent schoolchildren in Sri Lanka 8 months after the tsunami disaster found that of the total study sample, 11.0% (65) had abnormal scores and 21.2% (126) had borderline scores for the SDQ.…”
Section: Discussionmentioning
confidence: 53%
“…Due to the storm, 41% of the West Bank got covered with snow, and Gaza Strip was confronted with heavy flooding (www.apis.ps/up/1391593368. pdf Accessed August January 21,2016) 1 Thousands of people evacuated from their homes were sheltered in schools as the Gaza health ministry declared a state of "extreme emergency".…”
Section: Introductionmentioning
confidence: 99%